2009
DOI: 10.1111/j.1469-7610.2008.02025.x
|View full text |Cite
|
Sign up to set email alerts
|

A cluster randomized controlled trial of child‐focused psychiatric consultation and a school systems‐focused intervention to reduce aggression

Abstract: A cluster randomized controlled trial of child-focused psychiatric consultation and a school systemsfocused intervention to reduce aggression. J CHILD PSYCHOL PSYC , 50 (5)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
109
0
8

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 145 publications
(119 citation statements)
references
References 31 publications
2
109
0
8
Order By: Relevance
“…Of these interventions, four had an evaluation in which the research design criteria for Tiers I-III were met, yet there were no statistically significant positive results on any of our outcomes of interest: Girls in the Game (Bohnert and Ward, 2013), Lessons in Character (Hanson et al, 2012), Peer Group Connection (Johnson, Simon, and Mun, 2014), and Teacher-Child Interaction Training (Fernandez et al, 2015). In addition, four interventions had an evaluation in which the research design criteria for Tiers I-III were met, and there was a statistically significant negative result on an outcome interest: Creating a Peaceful School Learning Environment (Fonagy et al, 2009), on a measure of school climate and safety; Guiding Responsibility and Expectations for Adolescents for Today and Tomorrow (Farrell, 2008), on a measure of interpersonal competencies; PeaceBuilders (Flannery et al, 2003), on a measure of interpersonal competencies; and Social Problem Solving (Gottfredson, Jones, and Gore, 2002), on a measure of academic attainment. We have not included these eight interventions on our list of evidence-based interventions.…”
Section: Search Resultsmentioning
confidence: 94%
“…Of these interventions, four had an evaluation in which the research design criteria for Tiers I-III were met, yet there were no statistically significant positive results on any of our outcomes of interest: Girls in the Game (Bohnert and Ward, 2013), Lessons in Character (Hanson et al, 2012), Peer Group Connection (Johnson, Simon, and Mun, 2014), and Teacher-Child Interaction Training (Fernandez et al, 2015). In addition, four interventions had an evaluation in which the research design criteria for Tiers I-III were met, and there was a statistically significant negative result on an outcome interest: Creating a Peaceful School Learning Environment (Fonagy et al, 2009), on a measure of school climate and safety; Guiding Responsibility and Expectations for Adolescents for Today and Tomorrow (Farrell, 2008), on a measure of interpersonal competencies; PeaceBuilders (Flannery et al, 2003), on a measure of interpersonal competencies; and Social Problem Solving (Gottfredson, Jones, and Gore, 2002), on a measure of academic attainment. We have not included these eight interventions on our list of evidence-based interventions.…”
Section: Search Resultsmentioning
confidence: 94%
“…All students were involved in a larger research project studying school violence. 19 Nursing logs were available for 6 of 9 schools that had agreed to participate in the Fonagy et al 19 study. The study was reviewed and approved by the institutional review board of the Menninger Clinic.…”
Section: Methodsmentioning
confidence: 99%
“…For example, the prevalence of self-reported victimization at post-assessments was 23.3% 1 month after the termination of the Fear Not! intervention (Sapouna et al 2010), and 19.2% 2 years after the implementation of CAPSLE (Fonagy et al 2009). Evaluations of the KiVa intervention ) also demonstrated that rates of victimization did not decrease to zero: out of the total sample, 8.9% of children in Finland and 12.7% of Dutch children (Veenstra 2015) were still being victimized 1 and 2 years, respectively, after the intervention started.…”
mentioning
confidence: 99%